MAIN ASPECTS OF PERSONNEL MANAGEMENT OF INDUSTRIAL ENTERPRISES - Фурман, Діана (SWorldJournal, 2023)
The article examines the relationship and influence of personnel management on the achievement of effective enterprise activity, the formation of a personnel management system as a complete set of interacting elements, which ensures the adoption of econo